CONTRIBUTION TO THE PHYLOGENY OF THE PANGASIIDAE BASED ON MITOCHONDRIAL 12S RDNA - L. Pouyaud; R. Gustiano; G.G. Teugels (Indonesian Journal of Agricultural Science, 2004)
Catfishes are generally one of the economically important groups of fresh and brackish water fishes in the world. In many countries, they form a significant part of inland fisheries, and several species have been  introduced in fish culture. Judging from literature, the main constraint to cultivate wild species and to optimise the production of pangasiid catfishes is due to the poorly documented systematics of this family. In the present contribution, the phylogenetic relationships within Pangasiidae are studied to contribute to a better insight in their taxonomy and evolution. The genetic relatedness is inferred using mitochondrial 12S rDNA gene sequences. To resolve the phylogenetic position of Laides in this group of catfish, five genera of Asian and African Schilbeidae are also considered. The results showed that a species group (complex) could be clearly seen in the genetic tree. Pangasius is more derive than the other genera. By using approximate molecular clock/evolutionary calibration from  mitochondrial gene, a new episode of  speciation for the family marked explosive radiation about 5- 8 million years ago (mya). This adaptive radiation extended until the Late Pleistocene. Regarding the relationships between the Pangasiidae and Schilbeidae, two families show an allopatric distribution with slight overlap. The Pangasiidae occur mainly in Southeast Asia, while the Schilbeidae are seen mainly on the Indian subcontinent (including Myanmar) and Africa. It confirms the separation between  Schilbeidae and Pangasiidae occurred in the Early Miocene.